Development of an intervention to support patients and clinicians with advanced lung cancer when considering systemic anticancer therapy: protocol for the PACT study. Issue 7 (12th July 2017) - Anagnostou, Despina; Sivell, Stephanie; Noble, Simon; Lester, Jason; Byrne, Anthony; Sampson, Catherine; Longo, Mirella; Nelson, Annmarie
Abstract : Introduction: Patient-centred care is essential to the delivery of healthcare; however, this necessitates direct patient involvement in clinical decision-making and can be challenging for patients diagnosed with advanced non-small cell lung cancer where there may be misunderstanding of the extent of disease, prognosis and aims of treatment. In this context, decisions are complex and there is a need to balance the risks and benefits, including treatment with palliative intent. The aim of the PACT study is to identify the information and decision support needs of patients, leading to the development of an intervention to support patients with advanced lung cancer when considering treatment options. Methods and analysis: PACT is a five-stage, multimethod and multicentre study. Participants : Patients and health professionals will be recruited from three health boards. Methods : Non-participant observation of multidisciplinary team meetings (n=12) will be used to determine patients' allocation to treatment pathways (stage I). Non-participant observation of patient–clinician consultations (n=20–30) will be used to explore communication of treatment options and decision-making. Extent of participation in decision-making will be assessed using the Observing Patient Involvement in Shared Decision-Making tool. Interviews with patients (stage III) and their clinicians (stage IV) will explore the perception of treatment options and involvement in decision-making. Based on stages I–IV, an expert consensus meeting will finalise the content and format of the intervention. Cognitive interviews with patients will then determine the face validity of the intervention (stage V). Analysis : analysis will be according to data type and research question and will include mediated discourse analysis, thematic analysis, framework analysis and interpretative phenomenological analysis. Ethics and dissemination: Ethical approval has been granted. The study findings will contribute to and promote shared and informed decision-making in the best interest of patients and prudent healthcare. We therefore aim to disseminate results via relevant respiratory, oncology and palliative care journals and conferences.